Convergencia de FOFDM y LTE en redes de acceso de fibra óptica - Velásquez Vivas, Cintya Vanessa (2017)
We experimentally transmitted jointly FOFDM and LTE signals over one wavelength at optical access network. LTE up conversion at 1.5 GHz and FOFDM was left at baseband. Receiver sensibilities of -21.5 dBm and 21.8 dBm was found for FOFDM and LTE respectively at BER 10-3, after optimization of power LTE signal. The results show relationship between powers of two signals in this technics.